1991
DOI: 10.1115/1.2927890
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Incident Wake Conditions on the Mean Heat Transfer of an Airfoil

Abstract: The flow phenomena of wakes shed by upstream blade rows is a well-known problem in turbomachinery, which influences blade forces, vibrations, losses, and heat transfer. With respect to the heat load to turbine blades, this problem becomes even more complex because of the interaction between wake, potential flow, and the boundary layer along the surface of the airfoil. Experimentally evaluated mean heat transfer coefficients obtained under different unsteady initial conditions are reported. The heat transfer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Many investigations have been made to study the effect of unsteady wake and mainstream turbulence on the flow field and heat transfer coefficients of a downstream turbine blade. , , Blair et al (1989aBlair et al ( , 1989b, Blair (1992), Camci and Arts (1990), Dunn (1986), Dunn et al (1986Dunn et al ( , 1989Dunn et al ( , 1992, and Nirmalan and Hylton (1990) conducted experiments in actual gas turbine engines; whereas, Doorly (1988), Dullenkopf et al (1991), Dullenkopf and Mayle (1992), Rodi (1989, 1992), O'Brien and Capp (1989), Priddy and Bayley (1988), Wittig et al (1987Wittig et al ( , 1988, and Han et al (1993) did laboratory simulations of upstream unsteady wake conditions. Two techniques to produce unsteady wake have been used in laboratory simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations have been made to study the effect of unsteady wake and mainstream turbulence on the flow field and heat transfer coefficients of a downstream turbine blade. , , Blair et al (1989aBlair et al ( , 1989b, Blair (1992), Camci and Arts (1990), Dunn (1986), Dunn et al (1986Dunn et al ( , 1989Dunn et al ( , 1992, and Nirmalan and Hylton (1990) conducted experiments in actual gas turbine engines; whereas, Doorly (1988), Dullenkopf et al (1991), Dullenkopf and Mayle (1992), Rodi (1989, 1992), O'Brien and Capp (1989), Priddy and Bayley (1988), Wittig et al (1987Wittig et al ( , 1988, and Han et al (1993) did laboratory simulations of upstream unsteady wake conditions. Two techniques to produce unsteady wake have been used in laboratory simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Two techniques to produce unsteady wake have been used in laboratory simulations. Rodi (1989, 1992), and Priddy and Bayley (1988) used a squirrel cage type wake generator; whereas, Doorly (1988), Dullenkopf et al (1991), Dullenkopf and Mayle (1992), O'Brien and Capp (1989), Wittig et al (1987Wittig et al ( , 1988, and Han et al (1993) used a spoked wheel type wake generator. Mayle and Dullenkopf (1990) and Mayle (1991) recently developed a theory to incorporate unsteady effect into a steady flow analysis by introducing a time-averaged intermittency factor.…”
Section: Introductionmentioning
confidence: 99%
“…it was approximately homogeneous and isotropic. Dullenkopf, Schulz & Wittig (1991) and Liu & Rodi (1994a, b) performed heat transfer measurements of flow over turbine blades with incoming wakes, i.e. where the free-stream turbulence was concentrated in periodically passing wakes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the aforementioned results, it was found that an increase in wake passing frequency results in a shift of the transition region toward the leading edge due to increased turbulence activities. Dunn (1986), Dring et al (1986), Wittig et al (1988), Dullenkopf et al (1991), Liu and Rodi (1992), and Han et al (1993) Dunn (1986) and Doorly et al (1985) determined the heat transfer coefficient by using quick response sensors to detect the real time variation on the blade surface heat transfer induced by unsteady wakes. However, Liu and Figure shows a schematic picture of the wake flow within a multistage turbine in an absolute and relative frame of reference.…”
Section: Introductionmentioning
confidence: 99%